Pharmacokinetics of foscarnet after twice-daily administrations for treatment of cytomegalovirus disease in AIDS patients. - Taburet, A M (1992)
The pharmacokinetics of foscarnet were evaluated in 11 AIDS patients with cytomegalovirus disease after twice-daily infusion of 90 mg/kg of body weight for 2 weeks. All patients were hydrated during foscarnet infusion. Blood and urine samples were collected on days 1, 7, and 14 of therapy. Foscarnet concentrations were measured by high-pressure liquid chromatography. Despite large interindividual variations, no significant differences were seen between day 1, day 7, and day 14 concentrations in plasma. Mean peak and trough concentrations on day 14 of therapy were 605 +/- 118 and 52 +/- 59 microM, respectively. In all patients, peak concentrations were well above those necessary to inhibit cytomegalovirus. Pharmacokinetic parameters remained stable throughout the study. On day 14, the mean half-life was 3.4 h, total and renal clearances were 118 and 92 ml/min, respectively, and the volume of distribution was 0.6 liter/kg. These data and previous clinical trials demonstrate that this more convenient dosage regimen can be safely used for patients with cytomegalovirus disease. The side effects were comparable to those reported with other dosage regimens, although no renal impairment was seen in this study, probably because of the hydration.